2011
DOI: 10.1177/0363546511413372
|View full text |Cite
|
Sign up to set email alerts
|

When Do Rotator Cuff Repairs Fail? Serial Ultrasound Examination After Arthroscopic Repair of Large and Massive Rotator Cuff Tears

Abstract: Recurrent rotator cuff tears are not uncommon after arthroscopic repair of large and massive tears. These recurrent tears appear to occur more frequently in the early postoperative period (within the first 3 months) and are associated with inferior clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
190
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(206 citation statements)
references
References 37 publications
5
190
1
10
Order By: Relevance
“…It has been stated that intrinsic factors such as age of the patients, size of the tear, fatty degeneration and retraction of the affected tendons may play a role as predictors for recurrent tears after successful surgery [1][2][3][4][5][6][7]. Regardless, at this point, the only clear predictor that positively correlates with a higher recurrent tear rate seems to be the age of the patient at the moment of surgical intervention [2,5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated that intrinsic factors such as age of the patients, size of the tear, fatty degeneration and retraction of the affected tendons may play a role as predictors for recurrent tears after successful surgery [1][2][3][4][5][6][7]. Regardless, at this point, the only clear predictor that positively correlates with a higher recurrent tear rate seems to be the age of the patient at the moment of surgical intervention [2,5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Jo et al 9 report their results at 1 year postoperatively, which they acknowledge is too soon to demonstrate meaningful clinical outcomes, but should be sufficient to detect most failures to heal. 12,18 In fact, in this group of patients with tears measuring at least 30 mm anteroposterior in size, they observed a significantly lower failure rate in the PRP-treated group (20%) compared with the conventional group (56%).…”
mentioning
confidence: 79%
“…Regarding the existence of a new rupture, it was observed that most occur early in the postoperative period and that the initial rupture size and the age of the patient influence their incidence [35,41]. Jost et al [2] also found a relationship between the extent of fat infiltration of the infra-and supraspinatus muscles and the occurrence of new rupture [2].…”
Section: Complete Repairmentioning
confidence: 99%